2007
DOI: 10.1080/14756360701228558
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, antifungal and antioxidant screening of some novel benzimidazole derivatives

Abstract: Some novel benzimidazole derivatives were synthesized and their in vitro effects on rat liver microsomal NADPHdependent lipid peroxidation (LP) level, ethoxyresorufin O-deethylase (EROD) and antifungal activities were determined. A significant decrease in male rat liver microsomal LP level was noted by compounds 4c (52%), 4e (58%) and 4h (43%) at 10 23 M concentration. Compounds 4c (100.0%), 4h (100.0%), 5c (98.0%) and 5h (100.0%) inhibited the microsomal ethoxyresorufin O-deethylase (EROD) enzyme activity bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
38
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(40 citation statements)
references
References 12 publications
1
38
0
1
Order By: Relevance
“…Even some of the derivatives of benzimidazole have been clinically approved as summarized in Fig.1, like albendazole, mebendazole, thiabendazole as antihelmintics; omeprazole, lansoprazole, pantoprazole as proton pump inhibitors; astemizole as antihistaminic; enviradine as antiviral; candesarten cilexitil and telmisartan as antihypertensives and many lead compounds in a wide range of other therapeutic areas. Reported literature have shown the various substituted derivatives of benzimidazole nucleus exhibiting remarkable biological activity as antitumor/antiproliferative/anticancer activity [3][4][5][6][7][8][9][10][11][12][13][14], antimicrobial including anti-HIV [15][16][17][18][19], antioxidant [20][21][22][23] and cysticidal activities [24]. …”
Section: Introductionmentioning
confidence: 99%
“…Even some of the derivatives of benzimidazole have been clinically approved as summarized in Fig.1, like albendazole, mebendazole, thiabendazole as antihelmintics; omeprazole, lansoprazole, pantoprazole as proton pump inhibitors; astemizole as antihistaminic; enviradine as antiviral; candesarten cilexitil and telmisartan as antihypertensives and many lead compounds in a wide range of other therapeutic areas. Reported literature have shown the various substituted derivatives of benzimidazole nucleus exhibiting remarkable biological activity as antitumor/antiproliferative/anticancer activity [3][4][5][6][7][8][9][10][11][12][13][14], antimicrobial including anti-HIV [15][16][17][18][19], antioxidant [20][21][22][23] and cysticidal activities [24]. …”
Section: Introductionmentioning
confidence: 99%
“…This type of substituted thiosemicarbazides is an important class of intermediate used for the synthesis of five membered nitrogen-sulfur or nitrogen-oxygen heterocyclic compounds [1][2][3]. The chemistry of thiosemicarbazide complexes has received much attention owing to their medicinal properties [4,5] and their biological effects which include anti-inflammatory [6], antimycobacterial [7], antimicrobial [8], and antifungal [9]. In continuation of our previous work [11][12][13] ,we report herein the synthesis of Cd(II), Hg(II), Zn(II) and U(VI)O 2 2+ complexes derived from ligand namely, (Z)-N-benzoyl-N'-(2-oxo-2-(phenylamino)acetyl)carbamohydrazono-thioic acid (H 2 PABT).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous biological activities and functions have been described for benzimidazole nucleus viz. antihypertensive [9], antifungal [10], antioxidant [11], antiviral [12] and topoisomerase inhibitory [13] activities. Literature reports revealed that the benzimidazole derivatives also possessed antiviral activity against various strains of pathogenic viruses viz.…”
Section: Introductionmentioning
confidence: 99%